A mobility model for studying wireless communication and the complexity of problems in the model - Raymond Greenlaw (2018)
Wireless communication has become omnipresent in the world and enables users to have an unprecedented ability to communicate any time and any place. In this article, we propose a mobility model for studying wireless communication. The model incorporates elements such as users, access points, and obstacles so that it faithfully mimics the real environment. Interesting problems that have practical applications are posed and solved. More specifically, we study the complexity of three problems in a grid. The source reachability problem (SRP) models a situation in which we want to determine whether two access points can communicate at a certain time in a mobile environment. When users are involved in this situation, we call this problem the user communication problem (UCP). We show that SRP can be solved in O(max{d,t}m 2) time, where d is the number of obstacles, t is the time bound in the statement of the problem, and m is the number of access points; we show that UCP can be solved in O(max{d,t}m 4) time. The third problem called the user communication, limited source access problem (UCLSAP) studies a situation where we want to determine whether two users can communicate uninterruptedly during the duration of the model while considering battery-time limits of the access points. In contrast to the first two problems, we demonstrate that UCLSAP is intractable, unless P = NP. In conclusion, we briefly discuss the extension of our model to three dimensions and provide a list of open problems. © 2012 Wiley Periodicals, Inc. NETWORKS, 2012 Copyright © 2012 Wiley Periodicals, Inc.